Resurgent authoritarianism: the case of Russia's new NGO legislation. Issue 2 (3rd March 2016) - Flikke, Geir
Abstract : Following the protest demonstrations of the 2011–2012 electoral cycle, tensions between the limited modernization efforts of Medvedev and the resurgent authoritarianism of Putin have become increasingly manifest. These are seen not only in the relationship between society and the state, but also in the "para-constitutional" institutions of the dual state. This article argues that whereas Medvedev created an arena for liberalization within these para-constitutional structures, Putin has firmly rejected these policies, among other things by revising the 1995 law on NGOs amended in 2006. Using the perspective of the dual state, the article argues that with the introduction of the Law on Foreign Agents (2012), the original law draft On Public Control (2014), a key element in Medvedev's modernization program, was delayed and substantially altered. Together, these amendments create precarious conditions for NGOs, pressuring their independence by threats of dissolution and reducing the quality of civil control over state organs.